Cloning and Expression of Ketol-Acid Reductoisomerase (KARI) from Staphylococcus aureus - Rani, Y. Sandhya; Vijayalakshmi, P. (Asian Journal of Biological and Life Sciences, 2012)
Ketol-acid reductoisomerase (EC 1.1.1.86) catalyzes the conversion of 2-aceto-2-hydroxyacids to 2-keto-3hydroxyacids and their subsequent reduction by NADPH to 2, 3-dihydroxyacids. The ilvC gene encoding the Staphylococcus aureus enzyme was cloned and expressed in E. coli carrying pRSET vector. The enzyme expression was tested based on the blue white screening of the transformed colonies. The work was carried out to enable the over expression of KARI and thereby can be used as a drug target.